Exploring Sustainable Agricultural Techniques for Enhanced Pineapple Production in the Municipality of Bataraza, Palawan - Cabaña, Jonas P.; Dela Cruz, John Michael M. (Future Science / FSH-PH Publications, 2024)
Agriculture is one of the important sectors for economic development and food security all over the world. This study described and examined the sustainable agricultural techniques and practices in pineapple cultivation in the Municipality of Bataraza, Palawan. The study utilized descriptive correlational research which was participated by 30 pineapple farmers. Results of the study showed that Pineapple farmers efficiently utilized farming methods to increase the harvest and production of pineapple in Bataraza and gained profitable income that helped them to supplement the needs of their family. The production of pineapple depends largely on the farming methods and techniques they utilized.